Sifat Mikrobiologi, Serat Pangan, dan Kandungan Zat Gizi pada Bubuk Yogurt dari Kacang-Kacangan dan Salak Lokal yang Diproses melalui Fluidisasi: Microbiological Properties, Dietary Fiber, and Nutritional Content of Fluidized Bed-Dried Local Legumes and Salak Yogurt Powder - Nuraeni, Irma; Sumarto, Sumarto; Radiati, Ani (Amerta Nutrition, 2025)
Background: A major challenge in producing yogurt powder (YP) is the need for drying technology that maintains probiotic viability. In Small-Medium Enterprises (SMEs), adoption of such technologies to extend shelf life remains limited. The Fluidized Bed Dryer (FBD) provides a relatively simple method for producing YP from local legumes and salak. Objectives: To analyze the amount of Lactic Acid Bacteria (LAB), Dietary Fiber (DF), and Nutritional Content (NC) in local legumes and Salak Flour (SF) that is processed with a FBD. Methods: An experimental design with four treatments was applied: Mungbean (MYP), Garut Redbean (RYP), Manonjaya Salak-Mungbean (MS-MYP), and Manonjaya Salak-Garut Redbean Yogurt Powder (MS-RYP). Parameters measured included microbiological properties, DF, and NC (total calories, calories from fat, ash, moisture, carbohydrate, fat, protein, sugar, cholesterol, sodium, zinc, iron, and calcium). Differences in NC were analyzed using the Kruskal-Wallis test. Results: All YP samples contained LAB counts above the Indonesian National Standard (8 x 108 - 1 x 1010 cfu/g). DF content was higher in YP with added SF. Total ash, iron, and calcium were also higher in legume-based YP supplemented with SF, whereas sodium content was lower. Other nutrient levels were comparable between formulations with or without SF. Conclusions: Local legume YP added with SF contains higher levels of LAB, DF, total ash, iron, and calcium than legume YP alone.